Answer:
Keq = 3
Step-by-step explanation:
The reaction can be expressed as:
G6P → F8P
Keq = [F8P] / [G6P]
Because there are no products at the beginning, and there are no intermediates in this reaction, we can express the concentrations of the substances as followed:
- At the beginning of the reaction:
[G6P] = 0.8 M
[F8P] = 0.0 M
- At equilibrium, some G6P has turned into F8P, so its concentration can be expressed as a substraction of its original value:
[G6P] = 0.8 M - x
[F8P] = x = 0.6 M
We can rewrite [G6P]:
[G6P] = 0.8 M - 0.6 M = 0.2 M
Now that we know the values of [G6P] and [F8P] we can calculate Keq:
Keq = [F8P] / [G6P] = 0.6 / 0.2 = 3